Decentralization and local challenges in environmental resources policy: the Korean cases - Lee, Soonja, author; Mumme, Stephen, advisor; Lawrence, Robert M., committee member; Duffy, Robert, committee member; Campbell, Sue Ellen, committee member (Colorado State University. Libraries, 2006)
Since the 1970s, decentralization has been a vital reform agenda in developing countries. Korea illustrates this phenomenon. Its Democratic Declaration of June 29,1987 ushered in democratization and social mobilization, political processes that have encouraged decentralization. As Korea decentralizes, the impact of these reforms is felt across the policy spectrum. Yet the Korean government remains reluctant to allow the policy involvement of different social groups and subnational governments. This reality contributes to political and inter-governmental disputes. This problem is particularly acute in the governance of environmental resources. The leading questions in this study are whether local governments are motivated to engage in environmental resources governance and whether they are adequately supported by the central government. Inasmuch as decentralization is a dynamic policy experiment, this study employs a study design that examines the causes, process, and outcomes of decentralization in two important environmental resources cases, the Yeongwol Dam project and the Saemangeum tidal land reclamation project. These cases fit a most similar systems research design. The study employs archival research and qualitative interviewing to gather data and examine these cases. The evidence from Korea supports the view that decentralization is a significant trend, not a passing fad. Korea has taken significant steps towards decentralization since 1987. Yet it has largely focused on the transfer of administrative functions without devolving either political power or administrative necessities to such a degree as would alter Korea's prevailing policy centralism. The case studies show that a narrow focus on vertical reallocation of administrative functions fails to capture the complexity of Korean decentralization. They reveal that despite a limited commitment, political pressure from civil society and local governments is compelling the central government to continue decentralizing policymaking. Decentralization in environmental resources policy is yet in its infancy, but local governments have gained some functional competencies. Democratization and political decentralization are critical elements at the moment in advancing local challenges to the state. Overall, the findings suggest that progress in decentralizing environmental resources policy is based on a complex collective and political process that requires much more than just legal reform or transfer of administrative functions.
Keywords: public administration; environmental science